E-Commerce, Digital Economy, and Economic Development: An Analysis of Global Research Trends - Ana Rusmardiana (PT ARRUS Intelektual Indonesia, 2026)
This study maps the global scholarly landscape connecting e-commerce, the digital economy, and economic development, and identifies the field's intellectual structure, geographic centres, leading contributors, dominant themes, and emerging research frontiers over the period 2010–2026. A bibliometric analysis was conducted on 2,097 documents retrieved from Scopus, using metadata that included author affiliations and cited references. Performance analysis (annual output, productivity of authors, sources, and countries, and citation impact) was combined with science-mapping techniques: country collaboration networks, document co-citation, bibliographic coupling, keyword co-occurrence, thematic mapping, thematic evolution, a three-field plot, and trend-topic detection. Authors were disambiguated by Scopus identifier, and countries were extracted from affiliations. Annual output grew at roughly 15% per year, accelerating after 2019. The field is highly fragmented at author level (no author exceeds five documents) yet sharply concentrated geographically: China alone accounts for 937 of 2,097 documents, ahead of India, Indonesia, Russia, and the United States, although Chinese output is predominantly domestic (15% internationally co-authored) whereas US and UK output is majority-international and far more highly cited per paper. Co-citation analysis reveals three intellectual bases a behavioural/methodological base (technology-acceptance and survey-method classics), a digital-economy concept base, and an empirical e-commerce/rural-China base while bibliographic coupling identifies a single dominant research front of tightly linked digital-economy studies. Keyword and thematic analyses confirm a transversal e-commerce/digital-economy core surrounded by digital-transformation, rural-China, and artificial-intelligence clusters, with the field migrating toward cross-border, sustainable, and AI-enabled commerce. The paper offers an integrated, reproducible synthesis of a rapidly expanding literature, combining geographic, intellectual, and conceptual structure in a single study, and articulates a structured agenda for future inquiry.